(untitled) (Research, Society and Development, 2021)
To analyze the prevalence of syphilis cases in pregnant women in Brazil: a decade analysis. This is an epidemiological, observational, descriptive, documentary-type study with a quanti-qualitative approach, carried out through the survey of secondary data from SINAN, available on the electronic platform of the Information Technology Department of the Unified Health System (DATASUS) (Brazil, 2021). Gestational syphilis has been occurring frequently, highlighting some contributing factors, which are: lower middle class, low level of education, deficit in prenatal care, which is one of the most important for the outcome of intervening in the result, acquired in the protocol of the pregnant woman, thus guaranteeing a qualified assistance. Syphilis is a multifaceted pathology, with serious implications for the pregnant woman and her fetus. When acquired during pregnancy, it can lead to spontaneous abortion, fetal and neonatal death, prematurity and damage to the health of the newborn, with psychological and social repercussions. It is evident that health education is important in the outcome of a pregnancy, with the professional nurse being able to help the pregnant woman to live healthier and with all the necessary care during this period of her life. Therefore, it is necessary to carry out health promotion actions during pregnancy, focusing on self-care and prevention, as they reduce expenditure on more complex care and also reduce obstetric and neonatal complications that can be caused by syphilis.